STUDY OF COMMUNAL BASIUNI IMRAN ISLAMIC BOARDING SCHOOL WASTEWATER TREATMENT PLANT (WWTP) IN SAMBAS REGENCY - Andini, Medina; Apriani, Isna; Pramadita, Suci (Fakultas Teknik Universitas Tanjungpura, 2023)
Islamic Boarding School has a treatment capacity of 33 m3 and an area of 24 m2. Based on the results of initial wastewater quality tests on communal WWTP, the TSS, COD, and BOD parameters are above the quality standard threshold based on the Wastewater Quality Standard of the Minister of Environment Regulation Number 68 of 2016. This evaluation aims to determine the processing efficiency of communal WWTP and evaluate the processing unit in communal WWTP as well as alternative improvements that effectively reduce the parameters of pH, TSS, BOD, COD, and fatty oils. This research method is descriptive analytics, which analyses problems from data collected descriptively to find solutions to problems. The results of this evaluation show that the TSS, COD, and BOD parameters are above the quality standard threshold. The pH parameter increased by 3.6%, removal efficiency for BOD by 76.4%, COD by 71.9%, TSS by 84.3%, and oil grease by 91.9%. Alternative WWTP improvements are carried out by redesigning the Communal WWTP, which consists of calculating the equalization unit, precipitator I, anaerobic filter, Precipitator II, disinfection, and sludge thickener, Sludge digester, sludge drying bed and analysis of the Budget Plan Cost (RAB). The communal WWTP redesign requires a land area of 52.62 m2 with a processing capacity of 56.8 m3 and a cost budget plan of Rp.157,224,000.00. The redesign results of this evaluation can reduce environmental impacts due to domestic wastewater.